Leveraging Augmented Reality For Environmental Vocabulary Acquisition In Efl Contexts: Aligning With Sdgs In The Era Of Education 5.0 - Umar Umar; A Rahman; Nidya Fitri; Yana Karisma (STKIP Singkawang, 2025)
This study investigates the application of Augmented Reality (AR) to improve environmental vocabulary acquisition in English as a Foreign Language (EFL) context, aligning with the Sustainable Development Goals (SDGs) and Education 5.0. The objectives are to evaluate the effectiveness of AR in enhancing vocabulary acquisition and to explore students’ perceptions of AR-based learning. The study involved 72 eighth-grade students from SMP Negeri 4 Labuhan Badas, Sumbawa, Indonesia. A mixed-methods approach was employed, integrating quantitative analysis of vocabulary test scores and qualitative insights from open questionnaires. Students interacted with a 3D AR application that visualized environmental vocabulary categories, including beach terms, marine life, and fishing gear. Quantitative results revealed a statistically significant improvement in vocabulary scores (mean difference = 9.903, p < 0.001, Cohen’s d = 1.69), indicating the substantial impact of AR intervention. Qualitative findings highlighted increased motivation, comprehension, and retention due to AR’s immersive and interactive learning features, though technical barriers such as unstable internet were noted. The study implies that AR fosters experiential and contextualized learning, addressing gaps in traditional EFL vocabulary instruction. Beyond educational enhancements, AR supports SDG 4 by advancing quality education and SDG 14 by raising environmental awareness. These findings underscore AR’s ability to create engaging learning environments that bridge theoretical knowledge and practical application. Further research should explore AR's applicability across diverse subjects, regions, and student populations to maximize its interdisciplinary potential and address technical challenges for effective integration in global educational systems.